Determinants of Malaysian Islamic banks' profitability : a comparative study between wholesome Islamic banks and Islamic banking subsidiaries - Hussein, Hassan Abdikadir (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2020)
This study aims to examine the determinants of Islamic banking profitability in Malaysia by comparing between wholesome Islamic banking and Islamic banking subsidiaries The factors that are affecting bank profitability are capital ratio, liquidity ratio, asset quality, cost-to-income ratio, bank size, concentration, GDP and inflation; while profitability is measured by ROA and ROE. This study develops a model to identify a set of bank-specific, industry and macroeconomic determinants of bank profitability for 16 Islamic banks in Malaysia from 2009 to 2017. Having analysed the data by using appropriate methods, several financial ratios have been adopted from the empirical literature on bank profitability. Using a static model specification, random effect and fixed effect model are used to run the regression model using STATA econometric software, but a generalized least square (GLS) equation is employed as a corrective measure to solve the problem. The findings show that the bank-specific, industry and macroeconomic variables have a significant effect on Islamic bank profitability in Malaysia. Based on a static model specification, empirical analysis shows that the wholesome Islamic banks are more profitable than Islamic banking subsidiaries. the results also show that the determinants' significance varies between wholesome Islamic banking and Islamic banking subsidiaries. The results reveal that the capital ratio, liquidity and inflation have statistical significance on profitability for Islamic banking subsidiaries while the capital ratio, liquidity ratio, asset quality, cost-to-income ratio, bank size and concentration have statistical significance on profitability for wholesome Islamic banking.